PHRASEOLOGY OF THE VRBOVSKO LOCAL IDIOM - Mihaela Matešić (Fluminensia: Journal for Philological Research, 2006)
Semantic analysis of phrases and an analysis of linguistic convergence are conducted on the phraseological fund of the Vrbovsko local idiom. Phrases are semantically analysed with regard to monosemy, polysemy, homonymy, synonymy and antonymy. A conceptual analysis of phrases, based on the cognitive semantics approach, is conducted and the result is the grouping of phrases on the basis of the so-called concepts. Since the research was conducted on a dialectal corpus, the paper also offers an overview of the basic characteristics of the present-day state of the Vrbovsko local idiom. A dictionary of phrases of this local idiom can be found in the Appendix to this paper.